Towards the End of the Çatalhöyük East Settlement: A Faunal Approach - Pawłowska, Kamilla (Near Eastern archaeology, 2020)
The Çatalhöyük site produced material from the Neolithic occupation (7100 cal BCE-5900 cal BCE) through the Muslim period, including Bronze Age, Iron Age (Phrygian period), and Hellenistic periods. Twenty-five years of research have allowed us to study various ecofacts and artifacts, including animal and plant remains, human bones, pottery, stamp seals, and figurines. Faunal remains, which are the focus here, have been the subject of intense multidisciplinary research, particularly during the last decade. This has led to a greater understanding of Neolithic farmers’ subsistence patterns in the Anatolian region; the domestication, health and disease in past animal populations; spread of livestock; daily practices of animal food-related activities and management of waste; and of the ecological conditions of the region in which this community operated. Animals were also involved in social practice (Russell, Martin, and Twiss 2009; Pawłowska 2020; Pawłowska and Marciszak 2018; Der this issue) and used as a source of raw material in manufacturing.